Evaluating the Spring-Neap Tidal Effects on Chlorophyll-a Variations Based on the Geostationary Satellite - Xing, Qinwang; Yu, Huaming; Yu, Haiqing; Wang, Hui; Ito, Shin-ichi; Yuan, Chunxin (Frontiers in Marine Science, 2021)
Tides are the dominant hydrodynamic processes in most continental shelf seas and have been proven to have a significant impact on both marine ecosystem dynamics and biogeochemical cycles. In situ and satellite observations have suggested that the spring-neap tide results in fluctuations of chlorophyll-a concentrations (Chl-a) with a fortnightly period in some shelf waters. However, a large number of missing values and low observation frequency in satellite-observed Chl-a have been recognized as the major obstacle to investigating the regional pattern showing where and to what extent of the effects of spring-neap tide on Chl-a and the seasonal variations in the effects within a relatively large region. Taking Himawari-8 as an example, a simple algorithm appropriate for geostationary satellites was proposed in this study with the purpose of obtaining a tide-related daily climatological Chl-a dataset (TDCD) and to quantitatively estimate the effects of the spring-neap tide on Chl-a variations. Based on the Chl-a time series from TDCD, significant fortnightly signals of Chl-a fluctuations and high contribution together with high explanations of the fortnightly fluctuations for Chl-a variations were found in some specific inshore waters, especially in the East China Sea, Bay of Bengal, South China Sea, and northern Australian waters. The spring-neap tide was found able to induce the spatio-temporal fortnightly fluctuations of Chl-a with an annual amplitude of 12–33% of the mean in these inshore areas. Significant seasonal variations in the fortnightly fluctuation of Chl-a were observed in the temperate continental shelf regions, while levels remained relatively stable in the tropical waters. Further analysis implied that the spatio-temporal fortnightly fluctuations of Chl-a were closely associated with the tidal current differences between the spring and neap tides. Seasonal variations in the tidal current differences were found to be a key driving factor for seasonal fluctuations of the spring-neap tidal effects on Chl-a in the temperate continental shelf regions. This study provides a better understanding of tide-related marine ecosystem dynamics and biogeochemical cycles and is helpful in improving physical–biogeochemical models.